The Effect of Self-Confidence Moderation on the Effect of Emotional Intelligence on Employee Work Stress at PT. Orange Indonesia Mandiri Medan - Fadli, Ahmad; Hou, Amin; Juliansyah, Roni; Tambunan, Debora (Budapest International Research and Critics University, 2020)
The purpose of this study is to determine the effect of emotional intelligence on work stress and to determine the effect of emotional intelligence on work stress through self-confidence. This research was conducted at PT. Orange Indonesia Mandiri Medan by selecting 55 employees as respondents. Furthermore, data collection used a questionnaire with path analysis in proving the research hypothesis. The results showed that emotional intelligence had no positive and significant effect on work stress and emotional intelligence had no positive and significant effect on work stress through self-confidence. This means that when emotional intelligence and self-confidence are getting better, it will reduce employee work stress.